2021
DOI: 10.1038/s41598-021-99952-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-related polymorphisms and vitamin D levels as risk biomarkers of COVID-19 disease severity

Abstract: Vitamin D is a fundamental regulator of host defences by activating genes related to innate and adaptive immunity. Previous research shows a correlation between the levels of vitamin D in patients infected with SARS-CoV-2 and the degree of disease severity. This work investigates the impact of the genetic background related to vitamin D pathways on COVID-19 severity. For the first time, the Portuguese population was characterized regarding the prevalence of high impact variants in genes associated with the vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Recent studies have shown that 25(OH)D levels are related to mortality from COVID-19. The GC variant of rs2282679 in the gene encoding a vitamin D binding protein is associated with disease severity, and the DHCR7 rs12785878 variant associated with vitamin D deficiency has a higher prevalence in the Portuguese population than in Europe and may explain more severity of COVID-19 in the Portuguese population 102 . Some scholars have suggested that using the combination of dexamethasone and vitamin D in COVID-19 may improve the symptom of ARDS 103 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that 25(OH)D levels are related to mortality from COVID-19. The GC variant of rs2282679 in the gene encoding a vitamin D binding protein is associated with disease severity, and the DHCR7 rs12785878 variant associated with vitamin D deficiency has a higher prevalence in the Portuguese population than in Europe and may explain more severity of COVID-19 in the Portuguese population 102 . Some scholars have suggested that using the combination of dexamethasone and vitamin D in COVID-19 may improve the symptom of ARDS 103 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Although VDBP polymorphisms can induce the severity of infection [ 27 , 28 ], there is no strong evidence of an impact on CVD, because VDBP level is associated neither with disease outcome nor with vitamin D status. The GC gene variant also has no effect on 25(OH) D levels [ 29 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be partly explained by the potential protective effects of vitamin D, as described in the paper of Vanegas-Cedillo et al ( 1 ). In another study, polymorphisms in the DBP gene were also related to the infection severity of COVID-19 ( 7 ). The vitamin D total risk score ( DHCR7 ; CYP2R1 ; DBP ; CYP24A1 ; AMDHD1 ; SEC23A ) was associated with the serum 25OHD concentration.…”
Section: Vitamin D Binding Protein and Covid-19mentioning
confidence: 99%